Advances in Mathematical Fluid Mechanics: dedicated to Giovanni Paolo Galdi on the Occasion of his 60th Birthday - Rannacher, Rolf; Sequeira, Adélia (SpringerLink Bücher, 2010)
Isotropically and Anisotropically Weighted Sobolev Spaces for the Oseen Equation -- A New Model of Diphasic Fluids in Thin Films -- On the Global Integrability for Any Finite Power of the Full Gradient for a Class of Generalized Power Law Models #x003C; 2 -- Steady Flow Around a Floating Body: The Rotationally Symmetric Case -- On a Stochastic Approach to Eddy Viscosity Models for Turbulent Flows -- Numerical Study of the Significance of the Non-Newtonian Nature of Blood in Steady Flow Through a Stenosed Vessel -- A Priori Convergence Estimates for a Rough Poisson-Dirichlet Problem with Natural Vertical Boundary Conditions -- Vortex Induced Oscillations of Cylinders at Low and Intermediate Reynolds Numbers -- One-dimensional Modelling of Venous Pathologies: Finite Volume and WENO Schemes -- On the Energy Equality for Weak Solutions of the 3D Navier-Stokes Equations -- The ( #x002D; ) Coupled Fluid-Energy Systems -- A Potential-Theoretic Approach to the Time-Dependent Oseen System -- Regularity of Weak Solutions for the Navier-Stokes Equations Via Energy Criteria -- Looking for the Lost Memory in Diffusion-Reaction Equations -- Maximum Principle and Gradient Estimates for Stationary Solutions of the Navier-Stokes Equations: A Partly Numerical Investigation -- A Study of Shark Skin and Its Drag Reducing Mechanism -- Stability of Poiseuille Flow in a Porous Medium -- Towards a Geometrical Multiscale Approach to Non-Newtonian Blood Flow Simulations -- The Role of Potential Flow in the Theory of the Navier-Stokes Equations -- Small Perturbations of Initial Conditions of Solutions of the Navier#x2013;Stokes Equations in the L#x2013;Norm and Applications -- Streaming Flow Effects in the Nearly Inviscid Faraday Instability -- The Dirichlet Problems for Steady Navier-Stokes Equations in Domains with Thin Channels -- Existence of Weak Solutions to the Equations of Natural Convection with Dissipative Heating -- A Weak Solvability of the Navier-Stokes Equation with Navier#x2019;s Boundary Condition Around a Ball Striking theWall -- On the Influence of an Absorption Term in Incompressible Fluid Flows -- Adaptive FE Eigenvalue Computation with Applications to Hydrodynamic Stability -- Numerical Simulation of Laminar Incompressible Fluid-Structure Interaction for Elastic Material with Point Constraints -- On Stokes#x0027; Problem -- On a Semigroup Associated with a Modified Oseen Equation with Rotating Effect -- A New Approach to the Regularity ofWeak Lq-Solutions of Stokes and Similar Equations via the Cosserat Operator -- Large Time Behavior of Energy in Some Slowly Decreasing Solutions of the Navier-Stokes Equations -- A Selected Survey of the Mathematical Theory of 1D Flows -- A Numerical Method for Nonstationary Stokes Flow -- A New Criterion for Partial Regularity of Suitable Weak Solutions to the Navier-Stokes Equations -- An In Vitro Device for Evaluation of Cellular Response to Flows Found at the Apex of Arterial Bifurcations.